Sektorowy Program Operacyjny jako czynnik wzmacniający konkurencyjność polskich przedsiębiorstw wobec wyzwań globalizacji - Sutkowski, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The main aim of this article is to present the essence of Poland's and EU's development programme called "SPO-WKP" in the aspect of globalization process and European Union integration. The main goal of activities taken in the sphere of regional development policy in the EU is to reduce differences in economic development between the poorest and the richest regions of member countries. The author discusses the programme "SPO-WKP" as an example of regional development policy in Poland. This article analyzes problems arising from putting into force the above mentioned programme in the context of competitiveness of Polish enterprise and economy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 358-369